Advanced walet scaffolding nest design using modified high temperature stoneware / Syaza Abdul Rahim - Abdul Rahim, Syaza (2014)
Edible bird nest (EBN) known as the nests of Aerodramus Fuciphagus species (Walet) is built entirely from threads of their saliva, and normally it was collected for the famous Chinese delicacy bird's nest soup. In the market, EBN price grade by its form and size. From the reviewed work, it was discovered that the young Wale! are not able to build nest by their own. This led to an odd form that reduced its commercial values. Hence this was undertaken to introduce as- guide form to the young Walet to build a typical form that will increase its commercial values. Furthermore, the quality of EBN degraded due to the artificial surrounding. The existing scaffolding nest materials used plastic and silicon are not in standard size and gave negative effects on human health. Hence, the substitution of the existing scaffolding nest materials with nature materials may attract and create the natural habitat of Walet and increase the productivity of EBN. In this study, the design of the natural scaffolding nest was explored and it was determined that the form of the scaffolding has to be in the concave form for the ease of Wale! saliva deposition. The study on scaffolding nest materials was performed systematically and it was determined that the stoneware body with the composition of 30% calcium carbonate as fired at ll00°C/O.5h was finally used as scaffolding nest materials. The highest strength and water absorption are 16.94 N/mID2 and 24.67 %, respectively. Finally, the form of scaffolding nest was alike the natural supporter in limestone cave with guideline by MS 2334 (2011). The hook design also enhanced in order to adapt with ceramic materials brittleness. The modified stoneware scaffolding nest was successful installation in the Wale! house. The finding of this modified stoneware scaffolding nest will growth the productivity of the EBN hence it will increase the income of entrepreneur.